2021
DOI: 10.3390/jcm10132758
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Brolucizumab in Wet Age-Related Macular Degeneration: The REBA Study

Abstract: The aim of the present study was to determine the efficacy and safety of intravitreal brolucizumab therapy for neovascular age-related macular degeneration (AMD) in the real-world setting. The REBA study (real-world experience with brolucizumab in wet AMD) was a retrospective, observational, multicentric study that included 78 consecutive patients (105 eyes), with neovascular AMD, who received brolucizumab therapy. Both treatment-naive and switch-therapy patients were included. Switch therapy was based either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
74
5
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 24 publications
12
74
5
3
Order By: Relevance
“…In comparison, the SRF resolution in the BREW trial was superior (39.4%), while the PED resolution was suboptimal (6.4%). 16 At the same time, the IRF resolution in their eyes (36.8%) was similar to the current study. 16 Intraocular inflammation has been reported with other anti-VEGFs in the past, at an estimated rate of between 0.3% and 2.9% per injection.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In comparison, the SRF resolution in the BREW trial was superior (39.4%), while the PED resolution was suboptimal (6.4%). 16 At the same time, the IRF resolution in their eyes (36.8%) was similar to the current study. 16 Intraocular inflammation has been reported with other anti-VEGFs in the past, at an estimated rate of between 0.3% and 2.9% per injection.…”
Section: Discussionsupporting
confidence: 88%
“…16 At the same time, the IRF resolution in their eyes (36.8%) was similar to the current study. 16 Intraocular inflammation has been reported with other anti-VEGFs in the past, at an estimated rate of between 0.3% and 2.9% per injection. 18,19 The Fight Retinal Blindness!…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This demonstrates that the chosen treatment interval may not adversely influence the visual gain while fulfilling our anatomical objectives of a dry macula. In addition to our study, other real-life studies have demonstrated the effectiveness of brolucizumab injections in naïve, but also switch patients [17][18][19][20][21]. These data, combined with the present study, reinforce the results of the pivotal randomized controlled trial [11].…”
Section: Discussionsupporting
confidence: 86%